Advanced InversionRecovery Single Point Imaging for High Spatial Resolution and Quantitative Oxygen Imaging - Boris Epel; Irene Canavesi; Mrignayani Kotecha (Magnetic Resonance in Medicine, 2026)
ABSTRACT Purpose The partial pressure of oxygen (pO 2 ) in tissue is a tightly regulated physiological quantity. Hypoxia is a hallmark of many diseases, and changes in tissue pO 2 underline critical developmental, metabolic, and physiological processes. Electron paramagnetic resonance oxygen imaging (EPROI) has emerged as the most precise technique to image pO 2 in vitro and in vivo. EPROI uses linear relationship between the relaxation rates (R 1 or R 2 ) of the spin probe OXO71 and pO 2 . Methods The current gold standard for EPROI is inversion recovery electron spin echo (IRESE) sequence with radial k ‐space acquisition scheme, which is fast, provides high pO 2 resolution using T 1 imaging, but suffers from low spatial resolution, especially at higher oxygen concentrations. The other method, single‐point imaging (SPI), which uses Cartesian k ‐space acquisition scheme and free‐induction decay (FID) readout, provides higher spatial resolution but has lower signal‐to‐noise ratio (SNR) and lower pO 2 accuracy, especially for T 2 * imaging. In this work, we introduce advanced inversion‐recovery single‐point imaging (AIR‐SPI), which combines inversion‐recovery SPI (IR‐SPI) with multi‐point FID averaging in the spatial domain. We evaluate the performance of AIR‐SPI in phantoms and in vivo imaging of a fibrosarcoma (FSA) tumor in a mouse leg. Results We demonstrate 2–8‐fold SNR improvement and higher spatial resolution for AIR‐SPI compared to IR‐SPI and IRESE, especially for high oxygen concentrations. We also demonstrate higher pO 2 precision for AIR‐SPI. Conclusions AIR‐SPI offers improvements in image SNR, spatial, and oxygen resolution over all existing EPR oxygen imaging methods, without increasing imaging time. Importantly, it uses smaller RF power than echo‐based methods, which is crucial for scaling EPROI to human applications.